microRNAs delivered by small extracellular vesicles in MSCs as an emerging tool for bone regeneration - Runyuan Liu; Saixuan Wu; Wanqing Liu; Lina Wang; Ming Dong; Weidong Niu (Frontiers in Bioengineering and Biotechnology, 2023)
Bone regeneration is a dynamic process that involves angiogenesis and the balance of osteogenesis and osteoclastogenesis. In bone tissue engineering, the transplantation of mesenchymal stem cells (MSCs) is a promising approach to restore bone homeostasis. MSCs, particularly their small extracellular vesicles (sEVs), exert therapeutic effects due to their paracrine capability. Increasing evidence indicates that microRNAs (miRNAs) delivered by sEVs from MSCs (MSCs-sEVs) can alter gene expression in recipient cells and enhance bone regeneration. As an ideal delivery vehicle of miRNAs, MSCs-sEVs combine the high bioavailability and stability of sEVs with osteogenic ability of miRNAs, which can effectively overcome the challenge of low delivery efficiency in miRNA therapy. In this review, we focus on the recent advancements in the use of miRNAs delivered by MSCs-sEVs for bone regeneration and disorders. Additionally, we summarize the changes in miRNA expression in osteogenic-related MSCs-sEVs under different microenvironments.